AGRARIAN CONFLICT AND DISINTEGRATION: CHALLENGES FOR INDONESIA’S NATIONAL SECURITY - Erlinda Matondang (Indonesia Defense University, 2019)
In some countries, disintegration is happened because politization of disparities which had been their foundation in the beginning. Indonesia is precisely standing as a country with its disparities—which can be called as plurality—in ethnics, races, and faiths. As a country with plurality in its society, Indonesia is really fragile in facing domestic conflicts; one of them is agrarian conflicts. This article is written for understanding the relations between agrarian conflict and disintegration and also finding their position in Indonesian national security system. Thus, the object of the observation in this article is the relations between agrarian conflict and disintegration and their position in Indonesian national security system. The results of this observation bring the fact that agrarian conflicts can trigger disintegration among people and decrease legitimacy to the government. The possibility of disintegration is determined by subject-object dimension and government’s policies. Besides, agrarian conflicts can be classified as threats to Indonesian national security. There are four reasons why agrarian conflict should be placed as a threat to national security, i.e. conflict subject and object are Indonesia’s physical-based component which have to be protected; overlapping policy (institutional component) causing conflict; plurality issues; and anarchical behaviors often estimated as the best solution.Keywords: agrarian, disintegration, national security, conflict